The Effect of Work Environment and Communication on Employee Performance in The Quality Control Section at The Decoration Department of PT Lung Cheong Brothers Industrial Kragilan Serang - Achmad Rozi; Siti Rohaya; Denok Sunarsi; Azhar Affandi (Universitas Pamulang, 2023)
This study aims to determine the effect of the work environment and communication on the performance of quality control employees at PT. Lung Cheong Brothers Industrial decoration department. The research method used is quantitative research. The results of the quantitative analysis can be explained that the influence of the work environment and communication is very closely related to employee performance, the leadership of PT. Lung Cheong Brothers Industrial needs to pay attention to employee performance with an adequate work environment so that employees can work optimally.